The asthma Symptom Free Days Questionnaire: how reliable are patient responses?. (2nd November 2019) - Yawn, Barbara P.; Israel, Elliot; Wechsler, Michael E.; Pace, Wilson; Madison, Suzanne; Manning, Brian; Doros, Gheorghe; Fuhlbrigge, Anne
Abstract: Objective: Symptom free days are a widely used patient-reported outcome (PRO) in asthma clinical trials. We assessed the internal consistency of one instrument for this PRO, the Symptom Free Days Questionnaire (SFDQ), in a population of Black adults with asthma enrolled in the Blacks and Exacerbations on Long-acting beta agonists and Tiotropium (BELT) trial. Methods: We assessed responses to the SFDQ collected at baseline, 6 and 12 months as part of the BELT trial. The internal consistency of responses, specifically number of patient-reported days with symptoms in 14 days were compared to the number of patient-reported days with no symptoms in the same 14 days. Lin concordance correlation coefficients (Lin ccc) were calculated over time to assess "learning" and by age, sex, geographic location, and annual family income. Results: The internal consistency of the responses of the 1070 enrolled patients was consistently low over the 12 months of the study; varying from 43.8% at baseline to 52.1% at 12 months. This corresponded to Lin cccs of 0.33–0.32 over the study period. Internal consistency and the Lin ccc did not vary by age group, sex, geographic location or percent poverty. Concordance was slightly but not significantly higher at all time points in those with family annual income of ≥$50, 000 compared to those with lower annual incomes. Conclusions: The SFDQ did not work well in the BELT population of Black adults with asthma. Further validation is required before the SFDQ is used in other large clinical trials with any population.